Radio-technical characteristics of plasma and metal antennas mounted on aircrafts and spacecrafts (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
RT characteristics of plasma and metal antennas (VSWR, RP, gain, efficiency) installed on aircrafts and spacecrafts and their fragments in the software environment EMSS FEKO are investigated. It became possible to carry out higher-level 3D modeling of complex radiating structures. Comparative characteristics of the antennas, made of metal and gas-discharge cold plasma are shown. For the first time detected dual-band properties of plasma antennas mounted on a conical fragment of the aircraft. The influence of mercury vapor, usually introduced into the plasma antennas to facilitate the creation of a gas discharge, which to varying degrees modify the conductivity of the medium of the plasma antenna is investigated. As a result of the calculations elucidate the degree of influence configuration and size of mobile objects to internal and external parameters of the plasma and metal antennas in some of the most important microwave bands. Confirmed that the plasma antenna, mounted on mobile objects of complex configuration have a two to three times wider frequency range for VSWR and RP, compared to metal antennas.